2023
DOI: 10.1177/09636625231166255
|View full text |Cite
|
Sign up to set email alerts
|

Dunning–Kruger effect and flat-earthers: An exploratory analysis

Abstract: This article aims to analyze the factors influencing belief in a flat Earth. We focus on Spain, a country that sadly has some of the most relevant figures on this topic in the Spanish-speaking world. After a qualitative analysis of YouTube videos on the main channels on the subject, a survey was carried out on 1252 individuals. The results point to two conclusions. First is the presence of a considerable Dunning–Kruger effect among flat-earthers. There is a significant negative correlation between science lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In addition, analyses of data from Latin America have demonstrated that overconfident individuals are more likely to endorse authoritarian measures (Marisguia & Dias, 2021). Data POLITICAL KNOWLEDGE AND THE DKE 14 from Spain also suggests that overconfident individuals are more likely to believe in conspiracy theories, such as flat-earthism (Arroyo- Barrigüete et al, 2023). Finally, a study with 3,000 adults from the U.S. has shown that overconfidence is a substantive and statistically significant predictor of ideological extremism, vote abstention and partisan identification (Ortoleva & Snowberg, 2015).…”
Section: The Dunning-kruger Effect and Political Knowledgementioning
confidence: 97%
“…In addition, analyses of data from Latin America have demonstrated that overconfident individuals are more likely to endorse authoritarian measures (Marisguia & Dias, 2021). Data POLITICAL KNOWLEDGE AND THE DKE 14 from Spain also suggests that overconfident individuals are more likely to believe in conspiracy theories, such as flat-earthism (Arroyo- Barrigüete et al, 2023). Finally, a study with 3,000 adults from the U.S. has shown that overconfidence is a substantive and statistically significant predictor of ideological extremism, vote abstention and partisan identification (Ortoleva & Snowberg, 2015).…”
Section: The Dunning-kruger Effect and Political Knowledgementioning
confidence: 97%
“…On the basis of the data collected and analyzed, the article frames flat earthism as a paradigmatic case of superconspiracy, that is, of a farreaching theory capable of linking and including within itself a hierarchy of other, more circumscribed theories (Barkun 2003). To this end, flat earthism combines a heterogeneous network of discursive sources (Soares de Melo et al 2020), formulating an ambivalent narrative that on the one hand borrows the register of science (Arroyo- Barrigüete et al 2023;Mattos et al 2022) but rejects academic science, and on the other hand, borrows the language of religion, but draws on heterodox knowledge and spiritual currents proper to the cultic milieu (sensu Campbell 1972) that are proposed as alternatives to traditional and organized religions. In composing these sources of knowledge, the discourse of Italian flat earthism turns out to be marked by an anti-globalist rhetoric, in a twofold sense: first, because it argues against the acquisitions of science regarding the spherical shape of the planet, by supporting the thesis expressed by the formula "Earth is not a globe"; second, because it accredits an anti-intellectualist path of knowledge, accessible to the "common man" that aims to create a space of autonomy to oppose the processes of secularization and globalization in which the flat earthers see the implementation of the political, economic, and cultural project of building a future dystopian society, referred to as the New World Order.…”
Section: Introductionmentioning
confidence: 99%